-(v+1)-1=

Simple and best practice solution for -(v+1)-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(v+1)-1= equation:


Simplifying
-1(v + 1) + -1 = 0

Reorder the terms:
-1(1 + v) + -1 = 0
(1 * -1 + v * -1) + -1 = 0
(-1 + -1v) + -1 = 0

Reorder the terms:
-1 + -1 + -1v = 0

Combine like terms: -1 + -1 = -2
-2 + -1v = 0

Solving
-2 + -1v = 0

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -1v = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -1v = 0 + 2
-1v = 0 + 2

Combine like terms: 0 + 2 = 2
-1v = 2

Divide each side by '-1'.
v = -2

Simplifying
v = -2

See similar equations:

| 5y/2=40 | | 26x-8-16x+3=21x-7-11x+15 | | 6X*2+9X-6=0 | | 131=5(7+5x)+7x | | 3(n+2.5)=6.6 | | 0.142857*14= | | -2(w+3)-4(w+4)= | | 3(n+2.4)=6.6 | | 40x+(20x*1.5)=1500 | | 44+5y-19=17y-11-3y | | 2m+4c=28 | | 4x+84=6x | | 10x^2-4=746 | | 3x+15-7x=20-13x+9x-5 | | -0.6z-4=-3.85 | | 12a^3b^5/4a^6b^3 | | 8(3w-4)=12(2w+2) | | -2-5(1-5x)=-107 | | -2-9x^2=-83 | | 3X*2-5X-12=0 | | 3-4z=28 | | 3(2x-5)-10x= | | 4-3z=21 | | 0.375=-0.25x-0.6 | | 7k^2+10=38 | | 5(u-4)-9u= | | 15x^2-129x+72=0 | | 1/x=1.86257128811507 | | 1/x=0.02651.86257128811507 | | 5b-42=73 | | 6-14=z/-8 | | 1/x=1.91827966891323 |

Equations solver categories